The development of the ways of formation of the readiness of future higher school teachers for professional self-improvement in the process of extracurricular work - Кравченко, Володимир Миколайович (ScienceRise: Pedagogical Education, 2016)
The role and possibilities of extracurricular work in the process of formation of the readiness of future higher school teachers to professional self-improvement are elucidated in the article. The new scientific views on personal self-improvement are considered. It is noted, that professional self-improvement of the future teacher is the purposeful process of improvement of the level of own professional competence, comprehended by MA student and directed on maximal realization of he/her-self as a teacher according to personal program of self-improvement. The ways and features of professional self-improvement of future higher school teachers are demonstrated. The following forms of extracurricular work as the one of the ways of formation of readiness of future higher school teachers to professional self-improvement are indicated: scientific, creative-cognitive, professionally oriented one. The most effective ways as to preparation of future teachers to professional self-improvement are defined: participation in scientific clubs of professional direction, scientific researches within scientific topic of department, preparation of articles and theses of reports of scientific conferences, participation in trainings, master-classes of professional growth, meetings of clubs of pedagogical innovations, pedagogical-creative meetings, teaching-discussing platforms of pedagogical experience. It is stressed, that the complex organization of all types of extracurricular work of future teachers allows improve the level of creative activity of MA students that ensures their further professional and personal growth and self-improvement during the whole life